1998
DOI: 10.3354/dao032075
|View full text |Cite
|
Sign up to set email alerts
|

Palaemon elegans, an intermediate host in the life-cycle of Aggregata octopiana

Abstract: Based on immunological methods, the prawn Palaemon elegans apparently acts as the natural intermediate host for Aggregata octopiana, a coccidian that infects the cephalopod Octopus vulgaris. However, cross-reactivity with another coccidian, A. eberthi, was present in both sporogonic and merogonic stages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…In this study we found 100% of cultured cuttlefish fed with P. elegans were infected with A. eberthi at the end of the experiment. In an immunohistochemical study using polyclonal antibodies Arias et al (1998) concluded that the parasite species present in P. elegans was A. octopiana. However, there is a high level of cross-reactivity to polyclonal antibodies between A. octopiana and A. eberthi , giving rise to an uncertainty about specificity which could be resolved using monoclonal antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…In this study we found 100% of cultured cuttlefish fed with P. elegans were infected with A. eberthi at the end of the experiment. In an immunohistochemical study using polyclonal antibodies Arias et al (1998) concluded that the parasite species present in P. elegans was A. octopiana. However, there is a high level of cross-reactivity to polyclonal antibodies between A. octopiana and A. eberthi , giving rise to an uncertainty about specificity which could be resolved using monoclonal antibodies.…”
Section: Discussionmentioning
confidence: 99%